Evaluation of the Child-Friendly School Program at Adam's School Kindergarten Babelan District, Bekasi Regency - Fauziyah, Della; Muthi, Ibn; Sugiarti, Diyah Yuli (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The purpose of this study is to describe the Evaluation of Child Friendly School (CFS) Program at Adam's School Kindergarten with CIPP Evaluation Model. This research uses a qualitative approach with a descriptive method. The results of the study are: (1) The context component is in the form of program objectives according to needs, clear background and has a strong legal foundation. 2) The input component in the form of educator resources and education personnel is not all according to qualifications, the preparation of programs and learning media according to CFS principles, facilities and infrastructure must be improved, almost all program policies are running well. 3) The process component is learning according to CFS principles, the assessment process has not been seen with CFS principles, parent/guardian participation is cooperative. 4) The product component in the form of CFS program implementation shows the success of the program, namely the conformity of criteria and results, changes in children who are active in school and very happy in all activities, the benefits of the program are felt by the residents of the education unit So that the CFS program must be continued and can be applied in other institutions.